Uzbekistan is One of the Best and Safest Countries for Tourists (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the information related to the tourism potential of Uzbekistan is given as an example of safe tourism, the reforms carried out in this field during the years of independence and the prospective plans implemented by the state are detailed, as well as some scientific and practical suggestions are given. raised.